حدود مداولات المجلس الشعبي البلدي - هند بولبدة; إنصاف مخلوفي (My University, 2023)
Summary: After it became clear in detail the reality of overseeing the deliberations of the municipal people’s council, we can say that the municipal people’s assembly exercises its deliberations according to democracy within the framework of effective efficiency and this democracy is achieved through elections and the principle of collective management and the deliberations of the council proceed according to their own provisions through the calendar of sessions and the agenda by summoning the council according to the specified quorum the council’s deliberations cannot be held except to fulfill a number of conditions including the material conditions for holding sessions and sessions to the public and deliberations do not take place unless the discussions and voting processes are controlled and this deliberations is recorded through the session minutes and the deliberations extract is edited in Arabic and recorded on interconnected papers these deliberations are based on serveralcontrols including administrative control and judicial oversight . .......................... :الملخص بعدما تبين بالتفصيل واقع الرقابة على مداولات المجلس الشعبي البلدي, يمكننا القول ان المجلس الشعبي البلدي يمارس مداولاته وفق ديمقراطية في اطار الكفاءة الفعلية وتتحقق هذه الديمقراطية بالانتخاب وبمبدأ التسيير الجماعي, وتسيير مداولات المجلس وفق الاحكام الخاصة بها من خلال رزنامة الدورات وجدول الاعمال عن طريق استدعاء المجلس وفق النصاب المحددة ولا يمكن انعقاد مداولات المجلس الا لتحقيق جملة من الشروط منها الشروط المادية لانعقاد الدورات, وامانة الجلسة, كذلك شروط فتح جلسات المجلس للجمهور, ولا تجرى المداولات الا اذا تم ضبط المناقشات وعمليات التصويت, ويتم تدوين هذه المداولة من خلال محضر الجلسة, ويحرر مستخرج المداولة باللغة العربية, وتسجل على اوراق مترابطة ,وتقوم هذه المداولات على عدة رقابات منها الرقابة الإدارية والرقابة القضائية . ........................ Après avoir détaillé la réalité de la surveillance des délibérations de l’Assemblée populaire municipale, Nous pouvons dire que l’Assemblée populaire municipale conduit ses délibérations selon la démocratie dans le cadre de l’efficacité réelle et cette démocratie est réalisée par l’élection et par la manifestation de la conduite collective. Les délibérations du Conseil se déroulent conformément à ses propres dispositions, selon le calendrier des sessions et l’ordre du jour, en rappelant le Conseil conformément au quorum établi. Les délibérations du Conseil ne peuvent avoir lieu que pour réaliser, entre autres, les conditions physiques de la tenue des sessions. Et la sécurité de la réunion, aussi les conditions pour ouvrir les réunions du Conseil au public, et les délibérations ne se tiennent que si les débats et les processus de vote sont ajustés. Cette délibération est enregistrée dans le procès-verbal de la session, et l’extrait de la délibération est édité en arabe. Ces deliberations sent fondues, entre auras, sure le controlee administrative et judiciaries